2021
DOI: 10.1002/mds.28560
|View full text |Cite
|
Sign up to set email alerts
|

Is Adult‐Onset Dystonia a Rare Disease? Time for Population‐Based Studies

Abstract: Adult-onset dystonia 1 is considered a rare disease, a conclusion based on the relatively homogeneous low prevalence estimates provided by the majority of studies conducted between 1980 and 2011. Among the 19 studies performed in this period, 2-20 15 service-based/record linkage system studies and 3 population studies yielded crude prevalence estimates ranging between 3.0 and 43.0 × 10 5 , with estimates from most studies (10 of 18) narrowly ranging from 10.1 to 14.4 × 10 5 . [3][4][5][6]8,10,11,13,14 Only one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
(117 reference statements)
0
16
0
Order By: Relevance
“…A second clinical factor pointing towards a genetic cause might be onset in early-adulthood (21–40 years), which was described in 80 of the 179 (44.7%) patients with genetic dystonia and an initial presentation with AOIFD. As epidemiological data show that the prevalence of early-adulthood onset dystonia is much lower than late-adulthood onset dystonia,2 5 this might indicate that the percentage of 44.7% is relatively high, although detailed information is lacking here as well. Taken together, both a positive family history and onset in early adulthood might be, but currently not convincing, positive factors to suggest a genetic basis in a patient with an AOIFD.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A second clinical factor pointing towards a genetic cause might be onset in early-adulthood (21–40 years), which was described in 80 of the 179 (44.7%) patients with genetic dystonia and an initial presentation with AOIFD. As epidemiological data show that the prevalence of early-adulthood onset dystonia is much lower than late-adulthood onset dystonia,2 5 this might indicate that the percentage of 44.7% is relatively high, although detailed information is lacking here as well. Taken together, both a positive family history and onset in early adulthood might be, but currently not convincing, positive factors to suggest a genetic basis in a patient with an AOIFD.…”
Section: Discussionmentioning
confidence: 97%
“…Dystonia is a hyperkinetic movement disorder characterised by involuntary sustained or intermittent muscle contractions causing abnormal, often repetitive movements, postures or both 1. Dystonic syndromes are among the most common hyperkinetic movement disorders in adults with prevalence numbers ranging from 30 to 7320 per million across studies 2…”
Section: Introductionmentioning
confidence: 99%
“…Previous estimates of dystonia prevalence, from service‐ or population‐based studies, have varied between 6.1 and 70.1 per 100,000 in the former [ 31 , 32 ], to between 7.91 and 732 per 100,000 in the latter [ 15 , 17 ]. However, these approaches are likely to introduce bias, identifying only those seeking out or receiving clinical care, as well as underascertaining cases, suggesting that rates of dystonia within the population are higher than previously suggested [ 21 ]. In support of this, our results suggest an overall prevalence of dystonia syndromes of 1,219.8/100,000 (1.2%), which, given the unbiased nature of the case identification, suggests a more accurate population‐based value.…”
Section: Discussionmentioning
confidence: 99%
“…Recent advances in record‐linked population data repositories have led to increased opportunities for population‐based studies, providing more detailed epidemiological data across a range of neurological disorders [ 18 , 19 , 20 ]. There is a specific need to apply this population‐based approach to dystonia syndromes, particularly in relation to adult‐onset focal syndromes [ 21 ]. Use of data from several sources may address conflicting epidemiological estimates, and also has the potential to generate detailed information over several years and across diverse geographic areas, which is currently lacking in the field.…”
Section: Introductionmentioning
confidence: 99%
“…Dystonia is a disorder characterized by sustained or intermittent muscle contractions that typically cause abnormal movements or postures (Balint et al, 2018). It is among the most commonly observed movement disorders in clinical practice both in children and adults (Defazio & Berardelli, 2021; Fernandez‐Alvares & Nardocci, 2012). Recent studies have shown a striking co‐binding on DNA of YY1 with the dystonia‐associated gene THAP1.…”
Section: Dystoniamentioning
confidence: 99%